Inovasi Digital dalam Pengelolaan Administrasi Pendidikan - Lilis Romdon Nurhasanah; Dinar Sanjaya (JMPI: Jurnal Manajemen Pendidikan Islam, 2025)
This study analyzes digital innovation in educational administration management, including the types of innovations, supporting factors, obstacles, as well as their impacts and implications on efficiency, service quality, and decision-making. The research employs a qualitative method with a literature review approach. The results indicate that digital innovations, such as School Management Information Systems (SMIS), cloud-based applications, document digitization, and the integration of artificial intelligence, enhance administrative efficiency, accelerate decision-making, and improve transparency and accountability. The success of implementation is influenced by ICT infrastructure, staff competence, management support, and an adaptive organizational culture, while challenges include resistance to change, budget constraints, data security issues, and disparities in digital skills. The implementation of digital innovations has implications for developing institutional digital capacity, transforming work culture, and potentially improving overall educational quality.